(3GOGQI GdLhOI GdTGedI hNOeI GdYedGAs - (3eCehf SdjeGf(B, (3GdOQGOcIs ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2006)
(3eaGgje YGeI aj GOGQI GdLhOI GdTGedI GVGaI Gdi GOGQI GdLhOI cfXGe eJcGed h cPG GdGHYGO GdGSJQGJjLjI dGOGQI GdLhOI(B, (3bjGS LhOI GdSdY(B, (3GdQbGHI Ydi GdMhOI(B, (3MdbGJ JMSjf GdLhOI(B, (3GdLhOI aj NOeI GdYedGA(B, (3GOGQI GdLhOI GdTGedI aj Xd GdJMOjGJ GdGOGQjI GdMOjKI(B, (3GdGjRh (B9000 (3h aj GdNjQ LhGFR GOGQI GdLhOI GdTGedI(B.s
(3eQGLY U(B.301, (3edGMb U(B.277s
Keywords: (3GOGQI GdGYeGds; (3GdLhOIs